Competitive Action: A Bibliometric Literature Review - Gaol, Denada Faraswacyen L.; Maulina, Erna; Rizal, Muhamad; Purnomo, Margo (Journal of Ecohumanism, 2024)
This purpose of study discusses the development of competitive action research. Systematic review of the competitive action literature used, by selecting articles from Scopus and then using the bibliometric analysis method. Studies obtained from 2006 – 2023 through Rstudio. The result of this research is from 2006-2023, 66 documents were found, with an annual growth rate of 12.13%, average document citation of 18.42%, 161 authors with a single author of 12 documents, writing cooperation of 2.67% with an average international collaboration of 28.79%. The findings of this research is it was found that issues relating to competitive action are related to agency theory. These issues can be viewed in both positive and negative dimensions. In the literature that discusses competitive action, there is the use of various basic concepts that are analysed from various perspectives. This approach assumes that a person’s background, experience, personal characteristics and personality have an influence on the decision-making process. The use of these concepts aims to unravel and explain the dynamics of the relationship between stakeholders and management with the aim of reducing potential conflicts of interest. The findings are based on the available data and cannot represent the full scope of research investigations in this field. To date, there is no theory that encapsulates all aspects of competitive action. Despite these limitations, this research makes a substantial contribution to the field of competitive action by offering new insights and extensions to previous understandings. This research provides an understanding of various concepts related to competitive action. The comprehensive nature of the study and the identification of gaps in the literature provide meaningful recommendations for future research directions. The results of this study have the potential to support efforts to implement the concept of competitive action effectively, so that the prosperity (well-being) and sustainability of the company can be maintained and realized.